Activities and prospects of the Radioactive Materials Management Laboratory at the NCSR “Demokritos” - Savidou, A.; Ntalla, E.; Chanousis, A. (HNPS Advances in Nuclear Physics, 2019)
The Radioactive Materials Management Laboratory (RMML) was established in July 2013. The RMML is the sole laboratory in the country that holds the know-how in all the fields of radioactive waste management and decommissioning of nuclear facilities.The challenge for the Laboratory is the prospect of development of the Centralized Infrastructure of the country for Radioactive Waste at the NCSR D.